Metagenomic analysis of nitrogen‐cycling genes in upper Mississippi river sediment with mussel assemblages. Issue 5 (1st October 2018) - Black, Ellen M.; Chimenti, Michael S.; Just, Craig L.
Abstract: We investigated the impact of native freshwater mussel assemblages (order Unionoida) on the abundance and composition of nitrogen‐cycling genes in sediment of an upper Mississippi river habitat. We hypothesized that the genomic potential for ammonia and nitrite oxidation would be greater in the sediment with mussel assemblages, presumably due to mussel biodeposition products, namely ammonia and organic carbon. Regardless of the presence of mussels, upper Mississippi river sediment microbial communities had the largest genomic potential for nitrogen fixation followed by urea catabolism, nitrate metabolism, and nitrate assimilation, as evidenced by analysis of nitrogen cycling pathway abundances. However, genes encoding nitrate and nitrite redox reactions, narGHI and nxrAB, were the most abundant functional genes of the nitrogen cycling gene families. Using linear discriminant analysis (LDA), we found nitrification genes were the most important biomarkers for nitrogen cycling genomic potential when mussels were present, and this presented an opposing effect on the abundance of genes encoding nitric oxide reduction. The genes involved in nitrification that increased the most were amoA associated with comammox Nitrospira and nxr homologs associated with Nitrospira . On the other hand, the most distinctive biomarkers of microbial communities without mussels were norB and nrfA, as part of denitrification and dissimilatory nitrate reduction to ammonium pathways, respectively. Ultimately, this research demonstrates the impact of native mollusks on microbial nitrogen cycling in an aquatic agroecosystem. Abstract : Metagenomic sequencing of Upper Mississippi River sediments revealed a large genomic potential for nitrate metabolism and minor abundance of genes for anaerobic ammonia oxidation and DNRA pathways. The presence of a well‐established freshwater mussel assemblage in these sediments had significantly increased nitrification potential at the expense of DNRA and nitric oxide reduction. In support of these findings, amoA and nxr genes were the most predominant biomarkers of mussel bed, and these genes were associated with comammox Nitrospira and NOB Nitrospira, respectively.